High-absorption sanitary nursing pad and preparation method thereof

By introducing a modified zein and chitosan antibacterial liquid coating into the sanitary pad, along with a combination of PP fiber and composite wood pulp fiber absorbent layers, the problems of slow absorption and insufficient antibacterial properties of existing pads are solved, achieving a highly absorbent, antibacterial, and comfortable nursing effect.

CN120983213APending Publication Date: 2025-11-21SUZHOU MUNICIPAL HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511197445.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing disposable sanitary pads are slow to absorb high-protein liquids such as blood, have limited absorption capacity, and are prone to surface backflow, which increases the risk of infection. At the same time, their poor breathability affects the comfort and safety of users.

Method used

A skin-friendly surface layer is coated with an antibacterial solution containing modified zein, O-quaternary ammonium salt chitosan, oxidized white protein, and polysaccharides. Combined with a diversion layer of PP and ES fibers and an absorbent core layer of composite wood pulp fibers, a high-absorbency sanitary pad is prepared by hot air molding, which increases the absorption speed and antibacterial properties.

Benefits of technology

It improves the absorption rate and antibacterial properties of nursing pads, reduces the risk of infection, enhances user comfort and safety, and meets the requirements of green and low-carbon production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of nursing pads, in particular to a high-absorption sanitary nursing pad and a preparation method thereof.The high-absorption sanitary nursing pad is prepared by compounding a skin-friendly surface layer, a flow guide layer, an absorption core layer and a bottom layer and conducting hot air forming; the surface of the silk protein non-woven fabric is coated with the antibacterial liquid through a low-liquid-supply foam finishing technology, and the skin-friendly surface layer which is high in comfort level, antibacterial, capable of absorbing moisture in a one-way mode and breathable is prepared; mixing the modified zein, O-quaternary ammonium salt chitosan, oxidized bletilla striata polysaccharide and deionized water, adjusting the pH value of the system, and stirring to obtain an antibacterial solution; pP fibers and ES fibers are mixed, hot air non-woven processing forming is adopted, and a flow guide layer is obtained; the absorption core layer is prepared by taking composite wood pulp fibers, super absorbent resin and ES fibers as raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nursing pad technology, specifically a highly absorbent sanitary nursing pad and its preparation method. Background Technology

[0002] Sanitary pads are a common hygiene product that absorbs and controls body fluids, keeps skin clean and dry, and reduces the risk of infection. They are widely used in homes, nursing homes, and clinical settings. In clinical applications, such as post-radiation therapy care, prevention of pressure ulcers in the elderly, incontinence dermatitis, and treatment of postoperative pressure injuries, disposable sanitary pads are a common hygiene product.

[0003] Currently used disposable sanitary pads in clinical settings often have the following drawbacks: traditional cotton core materials absorb high-protein fluids such as blood slowly (>10 seconds) and have limited absorption capacity, leading to surface backflow and increasing the risk of infection; radiation therapy can cause skin fragility, i.e., thinning of the epidermis and increased skin sensitivity, and existing products often have limited breathability and contain fluorescent agents, easily causing dermatitis, resulting in poor user comfort and safety. Therefore, developing a sanitary pad that simultaneously possesses hemostatic, antibacterial, comfortable, and highly absorbent properties is of practical significance and economic value. Summary of the Invention

[0004] The purpose of this invention is to provide a highly absorbent sanitary pad and its preparation method to solve the problems in the prior art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0006] A method for preparing a highly absorbent sanitary pad includes the following steps:

[0007] S1: Modified zein, O-quaternary ammonium salt chitosan, oxidized white bile polysaccharide, and deionized water are mixed, the pH of the system is adjusted, and the mixture is stirred to obtain an antibacterial solution.

[0008] S2: Mix alkyl glycosides and antibacterial liquid, stir and foam, coat the foam onto the surface of silk protein nonwoven fabric, and dry to obtain a skin-friendly surface layer.

[0009] S3: Mix PP fibers and ES fibers, open, comb, lay in parallel web, and reinforce with hot air to obtain the flow guide layer;

[0010] S4: Soak composite wood pulp fibers in deionized water, stir and pulp, add ES fibers, stir, wet web, remove water, and obtain a blank; spray super absorbent resin on the blank, then cover it with another blank, needle-punch composite, and obtain an absorbent core layer;

[0011] S5: A skin-friendly surface layer, a diversion layer, an absorbent core layer, and a bottom layer are combined and hot-air molded to obtain a highly absorbent sanitary pad.

[0012] Furthermore, the bottom layer is a polyolefin film.

[0013] Furthermore, using deionized water as a solvent, the composition of the antibacterial solution is as follows: 3-6 g / L modified zein, 5-10 g / L O-quaternary ammonium chitosan, 4-8 g / L oxidized leucovorin, and pH 4.9-5.1.

[0014] Furthermore, the total mass ratio of the modified zein and O-quaternary ammonium chitosan to the mass ratio of oxidized leucovorin polysaccharide is 2:1.

[0015] Furthermore, in step S1, the working conditions for stirring are: temperature 20-30℃, time 9-10h; in step S2, the mass-to-volume ratio of alkyl glycoside and antibacterial solution is 2g:100mL; the working conditions for stirring and foaming are: stirring at 2000r / min for 2-3min.

[0016] Furthermore, in step S3, the mass ratio of PP fiber to ES fiber is 3:2; the working conditions for hot air reinforcement are: temperature 135℃ and time 2min.

[0017] Furthermore, in step S4, the mass ratio of composite wood pulp fiber, superabsorbent resin, and ES fiber is 5:2:3.

[0018] Furthermore, the preparation of O-quaternary ammonium salt chitosan includes the following steps:

[0019] (1) Mix chitosan and acetic acid solution, add anhydrous ethanol, add vanillin and ethanol mixture, keep warm at 60℃ for 19-20h, cool, adjust pH to neutral, filter, wash and dry to obtain modified chitosan.

[0020] (2) Mix modified chitosan and NaOH solution, add 2,3-epoxypropyltrimethylammonium chloride, stir at 78-82℃ for 2-3h, precipitate with anhydrous ethanol, filter and wash, extract in a Soxhlet extractor with anhydrous ethanol as solvent for 24h, dry, transfer to hydrochloric acid ethanol solution, stir at 18-25℃ for 22-24h, evaporate, add deionized water, precipitate with acetone, filter and dry to obtain O-quaternary ammonium salt chitosan.

[0021] Furthermore, the preparation of modified zein includes the following steps:

[0022] 1) Mix ethanol aqueous solution and zein, add deionized water, sonicate for 5 min, heat to 40℃ and evaporate by rotary evaporation, freeze dry to obtain zein nanoparticles;

[0023] 2) Under a nitrogen atmosphere, zein nanoparticles and an ethanol aqueous solution were mixed, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added, the pH was adjusted to 5, caffeic acid was added, the pH of the solution was adjusted to 5.5, the temperature was raised to 35-39℃ and kept at that temperature for 23-24 hours, the solution was placed in a dialysis bag and dialyzed with sodium chloride solution for 48 hours, and then freeze-dried to obtain polyphenol-modified zein.

[0024] 3) Mix cross-linked polylysine nanoparticles and hydrochloric acid solution, stir and disperse at 18-30℃, add a mixture of polyphenol-modified zein and ethanol aqueous solution, centrifuge at 10000rpm for 5min, wash and freeze dry to obtain modified zein.

[0025] Furthermore, the preparation of composite wood pulp fibers includes the following steps:

[0026] A. Immerse wood pulp fibers in sodium hydroxide aqueous solution and keep them at 33-37℃ for 20-25 min. Add chloroacetic acid, raise the temperature to 60-90℃ and keep them at 4-6 h. Filter, place in ethanol solution, adjust the pH to 7 with acetic acid, wash and dry to obtain carboxymethylated wood pulp fibers.

[0027] B. Under a nitrogen atmosphere, carboxymethylated wood pulp fiber and an aqueous ethanol solution are mixed, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are added, and cross-linked polylysine nanoparticles are added. The pH of the solution is adjusted to 5, the temperature is raised to 35-39℃ and kept at that temperature for 23-24 hours, and then washed and freeze-dried to obtain composite wood pulp fiber.

[0028] Furthermore, the preparation of cross-linked polylysine nanoparticles includes the following steps:

[0029] ε-polylysine and deionized water were mixed, and a mixture of hexamethylene diisocyanate and dichloromethane was added. The mixture was stirred at 18-30℃ for 23-24 hours, then heated to 53-57℃ and kept at that temperature for 23-24 hours. The mixture was then rotary evaporated and freeze-dried to obtain cross-linked polylysine nanoparticles.

[0030] Furthermore, a flexible electrode humidity sensor is built into the absorption core layer.

[0031] A flexible electrode humidity sensor is built into the absorbent core layer to collect humidity changes in real time. The intelligent system converts the humidity data into the actual amount of blood or other mixed liquids absorbed, realizing data collection, display, storage and alert functions, which facilitates real-time monitoring of the patient's bleeding volume.

[0032] Compared with the prior art, the beneficial effects of the present invention are:

[0033] This invention provides a highly absorbent sanitary pad and its preparation method. Through component and process design, a skin-friendly surface layer, a diversion layer, an absorbent core layer, and a bottom layer are composited and hot-air molded to prepare a highly absorbent sanitary pad that is antibacterial, hemostatic, and skin-friendly and comfortable.

[0034] Soft, skin-friendly, moisture-wicking, and breathable biodegradable silk protein nonwoven fabric was selected as the base fabric for the skin-friendly surface layer. An antibacterial liquid was coated onto the surface of the silk protein nonwoven fabric using a low-liquid-feed foam finishing process, creating a wettability gradient along the thickness direction of the fabric. This resulted in a highly comfortable, antibacterial, unidirectionally moisture-wicking, and breathable skin-friendly surface layer. Modified zein, O-quaternary ammonium salt chitosan, oxidized leucovorin polysaccharide, and deionized water were mixed, the pH of the system was adjusted, and the mixture was stirred to obtain the antibacterial liquid. The use of bio-based raw materials—zein, chitosan, and leucovorin polysaccharide—as raw materials for the preparation of the antibacterial liquid complies with current green and low-carbon production requirements.

[0035] The modified zein was prepared by chemically modifying zein nanoparticles with caffeic acid containing catechol groups to obtain polyphenol-modified zein. Then, the modified zein was prepared by introducing cationic antibacterial agents to crosslink polylysine nanoparticles through electrostatic self-assembly. The crosslinked polylysine nanoparticles were synthesized from ε-polylysine, which has good biocompatibility and cationicity, by adding hexamethylene diisocyanate as a crosslinking agent. Due to the non-covalent interaction between protein molecules and the adhesion effect of catechol groups, the binding force of modified zein on the surface of silk fibroin nonwoven fabric is improved, thereby enhancing the hemostatic and antibacterial properties of the skin-friendly surface.

[0036] In the skin-friendly surface treatment, chitosan is added to the antibacterial solution to further accelerate blood coagulation. To improve the solubility of chitosan, the amino groups are first protected by forming a Schiff base with vanillin and the amino groups on the chitosan. Then, quaternary ammonium salt 2,3-epoxypropyltrimethylammonium chloride is grafted onto the hydroxyl groups. The Schiff base is then removed using hydrochloric acid ethanol solution to obtain O-quaternary ammonium salt chitosan with good solubility and containing amino groups. By controlling the mass ratio of modified zein, O-quaternary ammonium salt chitosan, and oxidized leucovorin polysaccharide in the antibacterial solution, a network with both hydrophilicity and high adhesion is constructed based on cross-linking. Using foam finishing technology, the cross-linking solution is selectively coated onto one side of the silk protein nonwoven fabric, forming a wettability gradient in the thickness direction and giving it unidirectional moisture-wicking function. Among them, leucovorin polysaccharide can shorten prothrombin time and has a rapid hemostatic effect, playing a dual role of drug and adjuvant. It participates in the construction of the skin-friendly surface as a matrix and also exhibits good healing-promoting function, thereby improving the functionality of the skin-friendly surface.

[0037] To address the issues of low absorbency and long liquid penetration time in the application of the absorbent layer in nursing pads, PP (polypropylene) fiber and ES (polyolefin bicomponent) fiber are mixed and formed using hot air nonwoven processing. The absorbent core layer is prepared using composite wood pulp fiber, superabsorbent resin, and ES fiber as raw materials. To improve the antibacterial and absorbency properties of the absorbent core layer, the wood pulp fiber is modified by first carboxymethylating the wood pulp fiber, and then grafting crosslinked polylysine nanoparticles under the activation of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, thereby improving the antibacterial and superabsorbency properties of the absorbent core layer and enhancing the comfort of the nursing pad. Detailed Implementation

[0038] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0039] It should be noted that if the embodiments of the present invention involve directional indicators such as up, down, left, right, front, and back, these directional indicators are only used to explain the relative positional relationship and movement of components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0040] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0041] Example 1: A method for preparing a high-absorbency sanitary pad, comprising the following steps:

[0042] S1: Modified zein, O-quaternary ammonium salt chitosan, oxidized white bile polysaccharide, and deionized water are mixed, the pH of the system is adjusted, and the mixture is stirred to obtain an antibacterial solution.

[0043] Using deionized water as a solvent, the antibacterial solution consists of: 3 g / L modified zein, 5 g / L O-quaternary ammonium chitosan, 4 g / L oxidized leucovorin, and pH 4.9.

[0044] The mass ratio of the modified zein and O-quaternary ammonium chitosan to oxidized white bile polysaccharide is 2:1.

[0045] The working conditions for the stirring process are: temperature 20℃, time 10h;

[0046] The preparation of the O-quaternary ammonium salt chitosan includes the following steps:

[0047] (1) Mix 1g chitosan and 60mL of 10% acetic acid solution, add 20mL of anhydrous ethanol, add 7.3g vanillin and 10mL of ethanol mixture, reflux at 60℃ for 19h, cool, adjust pH to neutral, filter, wash and dry to obtain modified chitosan.

[0048] (2) Mix 1 mmol of modified chitosan and 40 mL of 0.5% NaOH solution, add 3 mmol of 2,3-epoxypropyltrimethylammonium chloride, stir at 78°C for 3 h, precipitate with anhydrous ethanol, filter, wash, extract in a Soxhlet extractor with anhydrous ethanol as solvent for 24 h, dry, transfer to 50 mL of 0.25 mol / L hydrochloric acid ethanol solution, stir at 18°C ​​for 24 h, evaporate, add 15 mL of deionized water, precipitate with acetone, filter, dry to obtain O-quaternary ammonium salt chitosan;

[0049] The preparation of the modified zein includes the following steps:

[0050] 1) Mix 40 mL of 75% ethanol aqueous solution and 1 g of zein, add 40 mL of deionized water, sonicate for 5 min, heat to 40 °C and remove 40 mL of solvent by rotary evaporation, freeze dry to obtain zein nanoparticles.

[0051] 2) Under a nitrogen atmosphere, 2g of zein nanoparticles and 50mL of 65% ethanol aqueous solution were mixed, 1g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.5g of N-hydroxysuccinimide were added, the pH was adjusted to 5, 2g of caffeic acid was added, the pH of the solution was adjusted to 5.5, the temperature was raised to 35℃ and kept at that temperature for 24h, the solution was placed in a dialysis bag (Mw=3500kDa), dialyzed with sodium chloride solution (pH=5.5, 0.1mol / L) for 48h, and then freeze-dried to obtain polyphenol-modified zein.

[0052] 3) Mix 0.2g of cross-linked polylysine nanoparticles with 20mL of 0.2mol / L hydrochloric acid solution, stir and disperse at 18℃, add 0.1g of polyphenol-modified zein and 10mL of 60% ethanol aqueous solution, centrifuge at 10000rpm for 5min, wash and freeze dry to obtain modified zein;

[0053] The preparation of composite wood pulp fibers includes the following steps:

[0054] A. Immerse 2g of wood pulp fiber in a 15% sodium hydroxide aqueous solution, keep it at 33℃ for 25min, add 1g of chloroacetic acid, heat to 60℃ and keep for 6h, filter, place in 100mL of 80% ethanol solution, adjust the pH to 7 with acetic acid, wash and dry to obtain carboxymethylated wood pulp fiber.

[0055] B. Under a nitrogen atmosphere, 3g of carboxymethylated wood pulp fiber and 80mL of 65% ethanol aqueous solution were mixed, 2g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1g of N-hydroxysuccinimide were added, and 2g of cross-linked polylysine nanoparticles were added. The pH of the solution was adjusted to 5, the temperature was raised to 35℃ and kept at that temperature for 24h, and the solution was washed and freeze-dried to obtain composite wood pulp fiber.

[0056] The preparation of the cross-linked polylysine nanoparticles includes the following steps:

[0057] Mix 2g of ε-polylysine and 20mL of deionized water, add 0.4g of hexamethylene diisocyanate and 2mL of dichloromethane, stir at 18℃ for 24h, raise the temperature to 53℃ and keep at that temperature for 24h, rotary evaporate and freeze dry to obtain cross-linked polylysine nanoparticles.

[0058] S2: Mix alkyl glycosides and antibacterial liquid, stir and foam, coat the foam onto the surface of silk protein nonwoven fabric 0.5mm, dry to obtain a skin-friendly surface layer;

[0059] In step S2, the mass-to-volume ratio of alkyl glycoside and antibacterial solution is 2g:100mL; the working conditions for stirring and foaming are: stirring at 2000r / min for 2min;

[0060] S3: Mix PP fibers and ES fibers, open, comb, lay in parallel web, and reinforce with hot air to obtain the flow guide layer;

[0061] In step S3, the mass ratio of PP fiber to ES fiber is 3:2; the working conditions for hot air reinforcement are: temperature 135℃ and time 2min.

[0062] S4: Soak composite wood pulp fibers in deionized water to prepare a 6% (w / w) composite wood pulp fiber solution. Stir and pulp the solution, add ES fibers, stir, wet web, remove water, and obtain a blank. Spray superabsorbent resin onto the blank, then cover it with another blank and needle-punch composite to obtain an absorbent core layer.

[0063] In the blank, the mass ratio of composite wood pulp fiber, superabsorbent resin, and ES fiber is 5:2:3;

[0064] S5: A skin-friendly surface layer, a diversion layer, an absorbent core layer, and a bottom layer are combined and hot-air molded to obtain a highly absorbent sanitary pad.

[0065] Example 2: A method for preparing a high-absorbency sanitary pad, comprising the following steps:

[0066] S1: Modified zein, O-quaternary ammonium salt chitosan, oxidized white bile polysaccharide, and deionized water are mixed, the pH of the system is adjusted, and the mixture is stirred to obtain an antibacterial solution.

[0067] Using deionized water as a solvent, the antibacterial solution consists of: 4 g / L modified zein, 8 g / L O-quaternary ammonium chitosan, 6 g / L oxidized leucovorin, and pH 5.

[0068] The mass ratio of the modified zein and O-quaternary ammonium chitosan to oxidized white bile polysaccharide is 2:1.

[0069] The working conditions for the stirring process are: temperature 25℃, time 9.5h;

[0070] The preparation of the O-quaternary ammonium salt chitosan includes the following steps:

[0071] (1) Mix 1g chitosan and 60mL of 10% acetic acid solution, add 20mL of anhydrous ethanol, add a mixture of 7.3g vanillin and 10mL ethanol, reflux at 60℃ for 19.5h, cool, adjust the pH to neutral, filter, wash and dry to obtain modified chitosan.

[0072] (2) Mix 1 mmol of modified chitosan and 40 mL of 0.5% NaOH solution, add 3 mmol of 2,3-epoxypropyltrimethylammonium chloride, stir at 80 °C for 2.5 h, precipitate with anhydrous ethanol, filter, wash, extract in a Soxhlet extractor with anhydrous ethanol as solvent for 24 h, dry, transfer to 50 mL of 0.25 mol / L hydrochloric acid ethanol solution, stir at 20 °C for 23 h, evaporate, add 15 mL of deionized water, precipitate with acetone, filter, dry, and obtain O-quaternary ammonium salt chitosan;

[0073] The preparation of the modified zein includes the following steps:

[0074] 1) Mix 40 mL of 75% ethanol aqueous solution and 1 g of zein, add 40 mL of deionized water, sonicate for 5 min, heat to 40 °C and remove 40 mL of solvent by rotary evaporation, freeze dry to obtain zein nanoparticles.

[0075] 2) Under a nitrogen atmosphere, 2g of zein nanoparticles and 50mL of 65% ethanol aqueous solution were mixed, 1g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.5g of N-hydroxysuccinimide were added, the pH was adjusted to 5, 2g of caffeic acid was added, the pH of the solution was adjusted to 5.5, the temperature was raised to 36℃ and kept at that temperature for 23.5h, the solution was placed in a dialysis bag (Mw=3500kDa), dialyzed with sodium chloride solution (pH=5.5, 0.1mol / L) for 48h, and then freeze-dried to obtain polyphenol-modified zein.

[0076] 3) Mix 0.2g of cross-linked polylysine nanoparticles with 20mL of 0.2mol / L hydrochloric acid solution, stir and disperse at 25℃, add 0.1g of polyphenol-modified zein and 10mL of 60% ethanol aqueous solution, centrifuge at 10000rpm for 5min, wash and freeze dry to obtain modified zein;

[0077] The preparation of composite wood pulp fibers includes the following steps:

[0078] A. Immerse 2g of wood pulp fiber in a 15% sodium hydroxide aqueous solution, keep it at 35℃ for 22min, add 1g of chloroacetic acid, heat to 70℃ and keep for 5h, filter, place in 100mL of 80% ethanol solution, adjust the pH to 7 with acetic acid, wash and dry to obtain carboxymethylated wood pulp fiber.

[0079] B. Under a nitrogen atmosphere, 3g of carboxymethylated wood pulp fiber and 80mL of 65% ethanol aqueous solution were mixed, 2g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1g of N-hydroxysuccinimide were added, and 2g of cross-linked polylysine nanoparticles were added. The pH of the solution was adjusted to 5, the temperature was raised to 37℃ and kept at that temperature for 23.5h, and the solution was washed and freeze-dried to obtain composite wood pulp fiber.

[0080] The preparation of the cross-linked polylysine nanoparticles includes the following steps:

[0081] Mix 2g of ε-polylysine and 20mL of deionized water, add a mixture of 0.4g of hexamethylene diisocyanate and 2mL of dichloromethane, stir at 25℃ for 23.5h, raise the temperature to 55℃ and keep at that temperature for 23.5h, rotary evaporate and freeze dry to obtain cross-linked polylysine nanoparticles.

[0082] S2: Mix alkyl glycosides and antibacterial liquid, stir and foam, coat the foam onto the surface of silk protein nonwoven fabric 0.5mm, dry to obtain a skin-friendly surface layer;

[0083] In step S2, the mass-to-volume ratio of alkyl glycoside and antibacterial solution is 2 g: 100 mL; the working conditions for stirring and foaming are: stirring at 2000 r / min for 2.5 min.

[0084] S3: Mix PP fibers and ES fibers, open, comb, lay in parallel web, and reinforce with hot air to obtain the flow guide layer;

[0085] In step S3, the mass ratio of PP fiber to ES fiber is 3:2; the working conditions for hot air reinforcement are: temperature 135℃ and time 2min.

[0086] S4: Soak composite wood pulp fibers in deionized water to prepare a 6% (w / w) composite wood pulp fiber solution. Stir and pulp the solution, add ES fibers, stir, wet web, remove water, and obtain a blank. Spray superabsorbent resin onto the blank, then cover it with another blank and needle-punch composite to obtain an absorbent core layer.

[0087] In the blank, the mass ratio of composite wood pulp fiber, superabsorbent resin, and ES fiber is 5:2:3;

[0088] S5: A skin-friendly surface layer, a diversion layer, an absorbent core layer, and a bottom layer are combined and hot-air molded to obtain a highly absorbent sanitary pad.

[0089] Example 3: A method for preparing a high-absorbency sanitary pad, comprising the following steps:

[0090] S1: Modified zein, O-quaternary ammonium salt chitosan, oxidized white bile polysaccharide, and deionized water are mixed, the pH of the system is adjusted, and the mixture is stirred to obtain an antibacterial solution.

[0091] Using deionized water as a solvent, the antibacterial solution consists of: 6 g / L modified zein, 10 g / L O-quaternary ammonium chitosan, 8 g / L oxidized leucovorin, and pH 5.1.

[0092] The mass ratio of the modified zein and O-quaternary ammonium chitosan to oxidized white bile polysaccharide is 2:1.

[0093] The working conditions for the stirring process are: temperature 30℃, time 9h;

[0094] The preparation of the O-quaternary ammonium salt chitosan includes the following steps:

[0095] (1) Mix 1g chitosan and 60mL of 10% acetic acid solution, add 20mL of anhydrous ethanol, add 7.3g vanillin and 10mL of ethanol mixture, reflux at 60℃ for 20h, cool, adjust pH to neutral, filter, wash and dry to obtain modified chitosan.

[0096] (2) Mix 1 mmol of modified chitosan and 40 mL of 0.5% NaOH solution, add 3 mmol of 2,3-epoxypropyltrimethylammonium chloride, stir at 82°C for 2 h, precipitate with anhydrous ethanol, filter, wash, extract in a Soxhlet extractor with anhydrous ethanol as solvent for 24 h, dry, transfer to 50 mL of 0.25 mol / L hydrochloric acid ethanol solution, stir at 25°C for 22 h, evaporate, add 15 mL of deionized water, precipitate with acetone, filter, dry, and obtain O-quaternary ammonium salt chitosan;

[0097] The preparation of the modified zein includes the following steps:

[0098] 1) Mix 40 mL of 75% ethanol aqueous solution and 1 g of zein, add 40 mL of deionized water, sonicate for 5 min, heat to 40 °C and remove 40 mL of solvent by rotary evaporation, freeze dry to obtain zein nanoparticles.

[0099] 2) Under a nitrogen atmosphere, 2g of zein nanoparticles and 50mL of 65% ethanol aqueous solution were mixed, 1g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.5g of N-hydroxysuccinimide were added, the pH was adjusted to 5, 2g of caffeic acid was added, the pH of the solution was adjusted to 5.5, the temperature was raised to 39℃ and kept at that temperature for 23h, the solution was placed in a dialysis bag (Mw=3500kDa), dialyzed with sodium chloride solution (pH=5.5, 0.1mol / L) for 48h, and then freeze-dried to obtain polyphenol-modified zein.

[0100] 3) Mix 0.2g of cross-linked polylysine nanoparticles with 20mL of 0.2mol / L hydrochloric acid solution, stir and disperse at 30℃, add 0.1g of polyphenol-modified zein and 10mL of 60% ethanol aqueous solution, centrifuge at 10000rpm for 5min, wash and freeze dry to obtain modified zein;

[0101] The preparation of composite wood pulp fibers includes the following steps:

[0102] A. Immerse 2g of wood pulp fiber in a 15% sodium hydroxide aqueous solution, keep it at 37℃ for 20min, add 1g of chloroacetic acid, heat to 90℃ and keep for 4h, filter, place in 100mL of 80% ethanol solution, adjust the pH to 7 with acetic acid, wash and dry to obtain carboxymethylated wood pulp fiber.

[0103] B. Under a nitrogen atmosphere, 3g of carboxymethylated wood pulp fiber and 80mL of 65% ethanol aqueous solution were mixed, 2g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1g of N-hydroxysuccinimide were added, and 2g of cross-linked polylysine nanoparticles were added. The pH of the solution was adjusted to 5, the temperature was raised to 39℃ and kept at that temperature for 23h, and the solution was washed and freeze-dried to obtain composite wood pulp fiber.

[0104] The preparation of the cross-linked polylysine nanoparticles includes the following steps:

[0105] Mix 2g of ε-polylysine and 20mL of deionized water, add 0.4g of hexamethylene diisocyanate and 2mL of dichloromethane, stir at 18-30℃ for 23-24h, raise the temperature to 53-57℃ and keep at that temperature for 23-24h, then rotary evaporate and freeze dry to obtain cross-linked polylysine nanoparticles.

[0106] S2: Mix alkyl glycosides and antibacterial liquid, stir and foam, coat the foam onto the surface of silk protein nonwoven fabric 0.5mm, dry to obtain a skin-friendly surface layer;

[0107] In step S2, the mass-to-volume ratio of alkyl glycoside and antibacterial solution is 2 g: 100 mL; the working conditions for stirring and foaming are: stirring at 2000 r / min for 3 min;

[0108] S3: Mix PP fibers and ES fibers, open, comb, lay in parallel web, and reinforce with hot air to obtain the flow guide layer;

[0109] In step S3, the mass ratio of PP fiber to ES fiber is 3:2; the working conditions for hot air reinforcement are: temperature 135℃ and time 2min.

[0110] S4: Soak composite wood pulp fibers in deionized water to prepare a 6% (w / w) composite wood pulp fiber solution. Stir and pulp the solution, add ES fibers, stir, wet web, remove water, and obtain a blank. Spray superabsorbent resin onto the blank, then cover it with another blank and needle-punch composite to obtain an absorbent core layer.

[0111] In the blank, the mass ratio of composite wood pulp fiber, superabsorbent resin, and ES fiber is 5:2:3;

[0112] S5: A skin-friendly surface layer, a diversion layer, an absorbent core layer, and a bottom layer are combined and hot-air molded to obtain a highly absorbent sanitary pad.

[0113] Comparative Example 1: Example 3 was used as the control group. The modified zein was replaced with zein, and the other processes were normal.

[0114] Comparative Example 2: Using Example 3 as the control group, chitosan was used to replace O-quaternary ammonium salt chitosan, while other processes were normal.

[0115] In the examples and comparative examples: the preparation of oxidized leucovorin polysaccharides includes the following steps:

[0116] Mix 1g of Bletilla striata polysaccharide and 1g of sodium periodate, stir at 18℃ in the dark for 8 hours, add 2mL of ethylene glycol and keep warm for 2 hours, dialyze through a dialysis bag (MWCO=3500Da) for 3 days, and freeze dry to obtain oxidized Bletilla striata polysaccharide.

[0117] In the examples and comparative examples, the bottom layer is a 50µm polypropylene film.

[0118] In the examples and comparative examples, the thickness of the flow guiding layer is 1 mm and the thickness of the absorption core layer is 1 mm.

[0119] Sources of raw materials used (for illustrative purposes only):

[0120] Silk protein nonwoven fabric (32g / m 2 Suzhou Xiancan Silk Biotechnology Co., Ltd.; Bletilla striata polysaccharide (98%, food grade); PP fiber (3dtex, 20mm); ES fiber (4dtex, 30mm, melting point 130℃); Superabsorbent polymer (SAP) (99%): Wuhan Jushun Chemical Co., Ltd.; Zea mayin (99%): Wuhan Shuer Biotechnology Co., Ltd.; ε-polylysine (99%): Shandong Pingju Biotechnology Co., Ltd.; Wood pulp fiber: Shandong Daoxin New Material Co., Ltd.; Chitosan C105799 Vanillin V100115, 2,3-epoxypropyltrimethylammonium chloride G298766, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride E106172, N-hydroxysuccinimide H109330, caffeic acid C108307, chloroacetic acid C485697, hexamethylene diisocyanate H106723, alkyl glycoside G462963: Aladdin reagent; sodium periodate, acetic acid, ethanol, NaOH, hydrochloric acid, acetone, sodium chloride, dichloromethane, analytical grade, commercially available.

[0121] Performance testing:

[0122] The nursing pads prepared in the examples and comparative examples were tested:

[0123] Air permeability: The air permeability test was carried out according to ASTM E96. When its air permeability value is higher than 800 g / m² / 24h, it is qualified; Blood absorption rate: The liquid absorption experiment was carried out with simulated blood (A7930: Solarbio Science & Technology Co., Ltd., Beijing). At 25°C, the prepared nursing pad was cut into 150 mm × 300 mm and laid flat. Take 30 mL of simulated blood, keep a distance of 0.5 cm from the nursing pad, and drip it into the front end of the nursing pad with a funnel equipped with a solenoid valve. Drip 5 mL each time, with an interval of 2 min, and drip 6 times in total. Record the contact time and the complete absorption time to obtain the liquid absorption rate; Antibacterial property: Escherichia coli was used as the test strain, and the plate method was used for testing; The obtained results are shown in Table 1;

[0124] Table 1

[0125]

[0126] The present invention provides a highly absorbent sanitary nursing pad and a preparation method thereof. Through the design of components and processes, the skin-friendly surface layer, the diversion layer, the absorption core layer, and the bottom layer are compounded and formed by hot air to prepare a highly absorbent sanitary nursing pad with antibacterial, hemostatic, and skin-friendly comfort. In Table 1, " / " indicates that this item was not tested.

[0127] Comparing Example 3 with Comparative Example 1, it can be seen that the modified zein is obtained by chemically modifying zein nanoparticles with caffeic acid containing catechol groups to obtain polyphenol-modified zein, and then introducing cationic antibacterial agent cross-linked polylysine nanoparticles by electrostatic self-assembly to prepare modified zein. The cross-linked polylysine nanoparticles are prepared from ε-polylysine with good biocompatibility and cationicity as raw materials, and a partially cross-linked polylysine nanoparticle with high stability is synthesized by adding a cross-linking agent hexamethylene diisocyanate. Due to the non-covalent interaction between protein molecules and the adhesion of catechol groups, the binding force of the modified zein on the surface of the silk fibroin non-woven fabric is improved, thereby enhancing the hemostatic and antibacterial properties of the skin-friendly surface layer.

[0128] Comparing Example 3 with Comparative Example 2, it can be seen that in the skin-friendly surface treatment, chitosan is added to the antibacterial solution to further accelerate blood coagulation. To improve the solubility of chitosan, the amino groups are first protected by forming a Schiff base with vanillin and the amino groups on the chitosan. Then, quaternary ammonium salt 2,3-epoxypropyltrimethylammonium chloride is grafted onto the hydroxyl groups. The Schiff base is then removed using hydrochloric acid ethanol solution to obtain O-quaternary ammonium salt chitosan with good solubility and containing amino groups. By controlling the use of deionized water as the solvent, the composition of the antibacterial solution is: 3-6 g / L modified zein, 5-10 g / L O-quaternary ammonium salt chitosan, 4-8 g / L oxidized leucovorin polysaccharide, and pH 4.9-5.1. Based on the cross-linking effect, a network with both hydrophilicity and high adhesion is constructed. The cross-linking solution is selectively coated on one side of the silk protein nonwoven fabric using foam finishing technology to form a wettability gradient in the thickness direction, giving it a unidirectional moisture-wicking function. Among them, Bletilla striata polysaccharide plays a dual role as a drug and adjuvant, participating in the construction of the skin-friendly surface layer as a matrix, and also showing good healing-promoting function, thus improving the functionality of the skin-friendly surface layer.

[0129] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the present invention's specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A method for preparing a highly absorbent sanitary pad, characterized in that, Includes the following steps: S1: Modified zein, O-quaternary ammonium salt chitosan, oxidized white bile polysaccharide, and deionized water are mixed, the pH of the system is adjusted, and the mixture is stirred to obtain an antibacterial solution. S2: Mix alkyl glycosides and antibacterial liquid, stir and foam, coat the foam onto the surface of silk protein nonwoven fabric, and dry to obtain a skin-friendly surface layer. S3: Mix PP fibers and ES fibers, open, comb, lay in parallel web, and reinforce with hot air to obtain the flow guide layer; S4: Soak composite wood pulp fibers in deionized water, stir and pulp, add ES fibers, stir, wet web, remove water, and obtain a blank; spray super absorbent resin on the blank, then cover it with another blank, needle-punch composite, and obtain an absorbent core layer; S5: A skin-friendly surface layer, a diversion layer, an absorbent core layer, and a bottom layer are combined and hot-air molded to obtain a highly absorbent sanitary pad.

2. The method for preparing a high-absorbency sanitary pad according to claim 1, characterized in that, Using deionized water as a solvent, the antibacterial solution consists of: 3-6 g / L modified zein, 5-10 g / L O-quaternary ammonium chitosan, and 4-8 g / L oxidized white bile polysaccharide, with a pH of 4.9-5.1; the mass ratio of the sum of the modified zein and O-quaternary ammonium chitosan to the mass of oxidized white bile polysaccharide is 2:

1.

3. The method for preparing a high-absorbency sanitary pad according to claim 1, characterized in that, In step S1, the working conditions for stirring are: temperature 20-30℃, time 9-10h; in step S2, the mass-to-volume ratio of alkyl glycoside and antibacterial solution is 2g:100mL; the working conditions for stirring and foaming are: stirring at 2000r / min for 2-3min.

4. The method for preparing a high-absorbency sanitary pad according to claim 1, characterized in that, In step S3, the mass ratio of PP fiber to ES fiber is 3:2; the working conditions for hot air reinforcement are: temperature 135℃ and time 2min.

5. The method for preparing a high-absorbency sanitary pad according to claim 1, characterized in that, In the preparation of the blank, the mass ratio of composite wood pulp fiber, superabsorbent resin, and ES fiber is 5:2:

3.

6. The method for preparing a high-absorbency sanitary pad according to claim 1, characterized in that, The preparation of the O-quaternary ammonium salt chitosan includes the following steps: (1) Mix chitosan and acetic acid solution, add anhydrous ethanol, add vanillin and ethanol mixture, keep warm at 60℃ for 19-20h, cool, adjust pH to neutral, filter, wash and dry to obtain modified chitosan. (2) Mix modified chitosan and NaOH solution, add 2,3-epoxypropyltrimethylammonium chloride, stir at 78-82℃ for 2-3h, precipitate with anhydrous ethanol, filter and wash, extract in a Soxhlet extractor with anhydrous ethanol as solvent for 24h, dry, transfer to hydrochloric acid ethanol solution, stir at 18-25℃ for 22-24h, evaporate, add deionized water, precipitate with acetone, filter and dry to obtain O-quaternary ammonium salt chitosan.

7. The method for preparing a high-absorbency sanitary pad according to claim 1, characterized in that, The preparation of the modified zein includes the following steps: 1) Mix ethanol aqueous solution and zein, add deionized water, sonicate for 5 min, heat to 40℃ and evaporate by rotary evaporation, freeze dry to obtain zein nanoparticles; 2) Under a nitrogen atmosphere, zein nanoparticles and an ethanol aqueous solution were mixed, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added, the pH was adjusted to 5, caffeic acid was added, the pH of the solution was adjusted to 5.5, the temperature was raised to 35-39℃ and kept at that temperature for 23-24 hours, the solution was placed in a dialysis bag and dialyzed with sodium chloride solution for 48 hours, and then freeze-dried to obtain polyphenol-modified zein. 3) Mix cross-linked polylysine nanoparticles and hydrochloric acid solution, stir and disperse at 18-30℃, add a mixture of polyphenol-modified zein and ethanol aqueous solution, centrifuge at 10000rpm for 5min, wash and freeze dry to obtain modified zein.

8. The method for preparing a high-absorbency sanitary pad according to claim 1, characterized in that, The preparation of composite wood pulp fibers includes the following steps: A. Immerse wood pulp fibers in sodium hydroxide aqueous solution and keep them at 33-37℃ for 20-25 min. Add chloroacetic acid, raise the temperature to 60-90℃ and keep them at 4-6 h. Filter, place in ethanol solution, adjust the pH to 7 with acetic acid, wash and dry to obtain carboxymethylated wood pulp fibers. B. Under a nitrogen atmosphere, carboxymethylated wood pulp fiber and an aqueous ethanol solution are mixed, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are added, and cross-linked polylysine nanoparticles are added. The pH of the solution is adjusted to 5, the temperature is raised to 35-39℃ and kept at that temperature for 23-24 hours, and then washed and freeze-dried to obtain composite wood pulp fiber.

9. A method for preparing a high-absorbency sanitary pad according to claim 7 or 8, characterized in that, The preparation of the cross-linked polylysine nanoparticles includes the following steps: ε-polylysine and deionized water were mixed, and a mixture of hexamethylene diisocyanate and dichloromethane was added. The mixture was stirred at 18-30℃ for 23-24 hours, then heated to 53-57℃ and kept at that temperature for 23-24 hours. The mixture was then rotary evaporated and freeze-dried to obtain cross-linked polylysine nanoparticles.

10. A highly absorbent sanitary pad, characterized in that, Prepared by the preparation method according to any one of claims 1-8.